The Relationship Between Fear of Missing Out (FoMO) and Learning Motivation Among Biology Education Students of the 2023 Cohort at the Faculty of Tarbiyah and Teacher Training UIN Alauddin Makassar - Amelia, Nanda; Taufiq, Ainul Uyuni; Hamansah (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the level of Fear of Missing Out (FoMO), learning motivation, and the relationship between the two in students of the Biology Education Study Program, class of 2023, Faculty of Tarbiyah and Teacher Training, UIN Alauddin Makassar. The study used a quantitative approach with a correlational design. The study subjects were 49 students selected through a saturated sampling technique. Data were collected using a Likert scale questionnaire and analyzed through descriptive statistics and Spearman's rho correlation. The results showed that students had a high level of FoMO and very high learning motivation. Although there was a tendency for a positive relationship between FoMO and learning motivation, the strength of the relationship was very weak (r = 0.070) and not statistically significant (p = 0.630 > 0.05). These findings indicate that students' FoMO levels were not significantly related to their learning motivation. Thus, the high level of student learning motivation in this study cannot be explained by FoMO levels, so it is likely influenced by other factors not analyzed in this study.